Evaluation of the Utility of Point-of-Care HIV Testing on a Canadian Internal Medicine Inpatient Unit. (2nd November 2017) - Lau, Lawrence; Wudel, Beverly; Lee, Eugene; Darraj, Majid; Richert, Quinlan; Trajtman, Adriana; Bresler, Kim; Bullard, Jared; Kasper, Ken; Becker, Marissa; Keynan, Yoav
Abstract : Point-of-care (POC) HIV testing has been shown to be an acceptable method for increasing HIV testing uptake. To date, no studies have examined the use of POC testing for routine HIV screening on the medicine inpatient unit. A prospective cross-sectional study was conducted over a three-month period in July, August, and October 2016 to evaluate the prevalence of undiagnosed HIV and the attitudes towards routine POC HIV testing. Patients admitted directly to medicine inpatient teaching units at a tertiary hospital in Winnipeg, Canada, were approached for participation. The POC HIV test was administered at the bedside. Reactive and indeterminate tests were confirmed with standard serological HIV testing. Participants were given a questionnaire regarding their attitudes towards POC testing on the unit. Although no cases of previously undiagnosed HIV were identified during the study period, only 35% of participants were found to have ever had HIV testing previously. The majority of participants were satisfied with the POC testing experience and would choose to have the POC testing again. Overall, the low rate of outpatient testing highlights the need for routine HIV testing on an inpatient basis.